Vascular complications in combination with endothelial dysfunction in patients with type 2 diabetes - Duisenbek, А.А.; Ablaihanova, N.T.; Kaldykarayeva, А.Т.; Yessenbekova, А.Е.; Mukhitdin, B.; Yessimsiitova, Z.B.; Kozhamzharova, L. (Fundamental and Experimental Biology, 2022)
This article presents information on diabetes mellitus and its complications and its relationship with the mechanism of endothelial dysfunction based on previous studies. Type 2 diabetes is a chronic disease that significantly increases the risk of cardiovascular complications. Endothelial dysfunction is considered an early indicator of the diagnosis of diabetic vascular complications. Although the exact pathogenetic mechanisms of ED in diabetes mellitus are still unclear, at the initial stage it turned out that they trigger the synthesis of nitric oxide, oxidative phosphorylation of mitochondria, and other processes. The subsequent main factors influencing the activation of this process are dyspledemia, oxidative processes, and inflammation. The paper considers current literature data on hyperglycemia, oxidative stress, and glycation end products with endothelial changes. A separate section is devoted to oxidative stress and their significance in the development of endothelial dysfunction in diabetes mellitus. In addition, in this review, special attention is paid to the main mechanisms involved in the occurrence of endothelial dysfunction, the production of large amounts of reactive oxygen species (ROS), inflammation, as well as their relationship with the main factors of cardiovascular risk.